Advertisements

Question 1: Factorize 4 x 2 − y 2 − 2y − 1

Question 1: Factorize 4 x^2{}- y^{2}-2y-1

How to factorize ?

Solution:

Given expression is

4 x^2{}- y^{2}-2y-1

= 4 x^{2}-(y^{2}+2y+1)

= (2x)^{2}-[y^{2}+2(y)(1)+(1)^{2}]

= [(2x)^{2}-(y+1)^{2}]

This now in   a^{2}-b ^{2}=(a+b)(a-b)

where,

2x stands for a

and

(y+1) stands for b

So, according to this formula;

=(2x-y-1)(2x+y+1)

 

 


  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  
  •  

You may submit a MCQ or maths problem with solution tips here in the comment box below! If you could not solve anyone, you may submit a MCQ or maths problem without solution as well. We will try our level best to solve it for you!

Your email address will not be published.

You may use these <abbr title="HyperText Markup Language">HTML</abbr> tags and attributes: <a href="" title=""> <abbr title=""> <acronym title=""> <b> <blockquote cite=""> <cite> <code> <del datetime=""> <em> <i> <q cite=""> <s> <strike> <strong>

All original content on these pages is fingerprinted and certified by Digiprove
Insert math as
Block
Inline
Additional settings
Formula color
Text color
#333333
Type math using LaTeX
Preview
\({}\)
Nothing to preview
Insert